DIAGNOSING CLEFT LIP PATHOLOGY IN 3D ULTRASOUND: A LANDMARKING-BASED APPROACH - Vezzetti, Enrico; Speranza, Domenico; Marcolin, Federica; Fracastoro, Giulia (Image Analysis and Stereology, 2015)
The aim of this work is to automatically diagnose and formalize prenatal cleft lip with representative key points and identify the type of defect (unilateral, bilateral, right, or left) in three-dimensional ultrasonography (3D US). Geometry has been used as a framework for describing facial shapes and curvatures. Then, descriptors coming from this field are employed for identifying the typical key points of the defect and its dimensions. The descriptive accuracy of these descriptors has allowed us to automatically extract reference points, quantitative distances, labial profiles, and to provide information about facial asymmetry. Eighteen foetal faces, ten of healthy foetuses and eight with different types of cleft lips, have been obtained through a Voluson system and used for testing the algorithm. Cleft lip has been diagnosed and correctly characterized in all cases. Transverse and cranio-caudal length of the cleft have been computed and upper lip profile has been automatically extract to have a visual quantification of the overall labial defect. The asymmetry information obtained is consistent with the defect. This algorithm has been designed to support practitioners in identifying and classifying cleft lips. The gained results have shown that geometry might be a proper tool for describing faces and for diagnosis.